2018
DOI: 10.5513/jcea01/19.1.2035
|View full text |Cite
|
Sign up to set email alerts
|

Grain yield and its components in triticale grown on a pseudogley soil

Abstract: A field trial was conducted on an acid pseudogley soil during the 2011/12, 2012/13 and 2013/14 growing seasons to evaluate grain yield and its components in four triticale cultivars ('Favorit', 'Tango',. The highest values of grain yield, 1,000-grain weight, number of grains per spike, spike length and plant height in all cultivars were obtained in the year characterised by moderate temperatures during grain filling and high amounts of rainfall in the second part of the growing season. 'Favorit' gave the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…The results of this study showed that the influence of nitrogen fertilization on the grain yield, components of the yield and the quality of grain, do not depend only on the dose of fertilizers, but also on the climatic conditions, as Janušauskaitė (2013), Ivanova and Kirchev (2014), Djurić et al (2015), Madić et al (2018), Terzić et al (2018 and Đekić et al (2019) had confirmed previously in their researches. (Djekić et al 2012;, as well as many other authors, point out that the high quality of grain and the best triticale yields are obtained in the years with warm bright spring weather conditions and cold summers without excessive precipitation during the grain filling stage, which is in agreement with this study.…”
Section: Resultssupporting
confidence: 70%
“…The results of this study showed that the influence of nitrogen fertilization on the grain yield, components of the yield and the quality of grain, do not depend only on the dose of fertilizers, but also on the climatic conditions, as Janušauskaitė (2013), Ivanova and Kirchev (2014), Djurić et al (2015), Madić et al (2018), Terzić et al (2018 and Đekić et al (2019) had confirmed previously in their researches. (Djekić et al 2012;, as well as many other authors, point out that the high quality of grain and the best triticale yields are obtained in the years with warm bright spring weather conditions and cold summers without excessive precipitation during the grain filling stage, which is in agreement with this study.…”
Section: Resultssupporting
confidence: 70%
“…Mineral fertilisers led to a significant increase in grain weight per spike (treatments II and III), which was highest in the treatment with mineral fertilisers and lime. Grain weight per spike is a yield component dependent on genotype (Knežević et al 2019) as well as on nutrition, plant density, soil fertility and other factors in the agroecosystem during vegetative growth and development (Dimitrijević et al 2009, Madić et al 2018). Significant differences in barley grain weight depending on year and genotype were also reported by Đekić et al (2017).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the necessary reserve for the spring part of the vegetation, winter precipitation greatly influenced the distribution of easily accessible nitrogen in the soil [11,30,31]. Many authors state that the yields are strongly modified by the environment of different temperatures and weather conditions [13,16,29,[32][33][34][35][36]. It is rarely the individual influence of one stress factor, and often development of plants occurs under the combination of a few different stresses which makes for a more complex evaluation of adaptability.…”
Section: Meteorological Conditionsmentioning
confidence: 99%
“…The highest average yield of 4.024 t ha −1 was recorded in treatment N 80 P 100 K 60 and it was significantly higher than the yield in untreated treatment−control (1.150 t ha −1 ). To achieve high and stable grain yields, new cultivars demand more precise and complex NPK nutrition [18,32,33]. Nitrogen application has a crucial role.…”
Section: Grain Yield 1000 Grain Weight and Hectolitre Massmentioning
confidence: 99%
See 1 more Smart Citation